Manajemen Badan Usaha Milik Desa Makmur Sejahtera di Desa Serang Kecamatan Karangreja Kabupaten Purbalingga - Fathurochman, Anas; Sutikno, Chamid; Amanda, Ariesta; Pribadi, Indah Ayu Permana; Milata, Chanifia Izza (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
In research that has been carried out with the title "Management of Prosperous Village-Owned Enterprises in Serang Village, Karangreja District, Purbalingga Regency" This research is based on the phenomenon that exists in Purbalingga Regency, where Purbalingga Regency has several sub-districts and villages in Purbalingga Regency, namely in business villages which are called Village-Owned Enterprises, which have a good and significant impact starting from human resources and natural resources, have increased from year to year, especially in Serang Village, Karangreja District, Purbalingga Regency with the progress of BUMDes Makmur Sejahtera. This research uses qualitative methods and is supported by methods using informant selection techniques, data collection using observation, interviews and documentation. The results found that the existence of the Management of Makmur Sejahtera Village-Owned Enterprises, has shown the difference between the existence of BUMDes and the absence of BUMDes, this is shown by several factors, namely starting to increase business units, adding PADes, as well as providing prosperity for the community around BUMDes Makmur Sejahtera , this is proven by the existence of jobs for local youth and for traders around the village and around BUMDes Makmur Sejahtera, this cannot be denied by the concept of POAC. The conclusion of this research is that the implementation of Village-Owned Enterprise Management has succeeded in making a significant difference to the village and community, this is supported by planning, structural organization and the existence of good control and supervision, this is what makes BUMDes Makmur Sejahtera progress. and as an example from other BUMDes in the Purbalingga Regency area.